Onset time of hyperkalaemia after angiotensin receptor blocker initiation: when should we start serum potassium monitoring?. (22nd November 2013) - Park, I.‐W.; Sheen, S. S.; Yoon, D.; Lee, S.‐H.; Shin, G.‐T.; Kim, H.; Park, R. W.
Summary What is known and objective Angiotensin receptor blockers (ARBs) frequently induce hyperkalaemia in high‐risk patients. Early detection of hyperkalaemia can reduce the subsequent harmful effects. This study was performed to examine the onset time of hyperkalaemia after ARB therapy. Methods We carried out a retrospective analysis to determine the onset time of hyperkalaemia (serum potassium >5·5 mm) among hospitalized patients newly starting ARB therapy between 2004 and 2012, in a tertiary teaching hospital. Predefined possible risk factors and concomitant medications were evaluated. Results and discussion During the 97‐month study period, a total of 4267 hospitalized patients started ARBs as new drugs and 225 patients showed hyperkalaemia. A significantly increased risk of hyperkalaemia was detected among patients with a high baseline potassium [odds ratio (OR) 6·0] and those who took non‐potassium‐sparing diuretics (OR 2·2) or potassium supplements (OR 1·6). A high glomerular filtration rate (GFR) was associated with a lower risk of hyperkalaemia (OR 0·992). Fifty‐two percentage of hyperkalaemic events occurred within the first week after initiation of ARB therapy. The highest frequency of hyperkalaemia occurred on the first day after initiation of ARBs. Hyperkalaemia occurred earlier in patients with a high baseline serum potassium level, reduced GFR, diabetes and in those without heart failure. What is new and conclusion Hyperkalaemia occurs most frequently at the beginning of ARB therapy in hospitalized patients. Monitoring of serum potassium and estimated GFR after initiation of ARBs should be started within a few days or not later than 1 week, especially in patients with risk factors.